Prediction of readmissions and mortality in patients with heart failure: lessons from the IMPEDANCE‐HF extended trial. (10th August 2018) - Kleiner Shochat, Michael; Fudim, Marat; Shotan, Avraham; Blondheim, David S.; Kazatsker, Mark; Dahan, Iris; Asif, Aya; Rozenman, Yoseph; Kleiner, Ilia; Weinstein, Jean Marc; Panjrath, Gurusher; Sobotka, Paul A.; et al.
Abstract: Aims: Readmissions for heart failure (HF) are a major burden. We aimed to assess whether the extent of improvement in pulmonary fluid content (ΔPC) during HF hospitalization evaluated by lung impedance (LI), or indirectly by other clinical and laboratory parameters, predicts readmissions. Methods and results: The present study is based on pre‐defined secondary analysis of the IMPEDANCE‐HF extended trial comprising 266 HF patients at New York Heart Association Class II–IV and left ventricular ejection fraction ≤ 35% randomized to LI‐guided or conventional therapy during long‐term follow‐up. Lung impedance‐guided patients were followed for 58 ± 36 months and the control patients for 46 ± 34 months ( P < 0.01) accounting for 253 and 478 HF hospitalizations, respectively ( P < 0.01). Lung impedance, N‐terminal pro‐brain natriuretic peptide, weight, radiological score, New York Heart Association class, lung rales, leg oedema, or jugular venous pressure were measured at admission and discharge on each hospitalization in both groups with the difference defined as ΔPC. Average LI‐assessed ΔPC was 12.1% vs. 9.2%, and time to HF readmission was 659 vs. 306 days in the LI‐guided and control groups, respectively ( P < 0.01). Lung impedance‐based ΔPC predicted 30 and 90 day HF readmission better than ΔPC assessed by the other variables ( P < 0.01). The readmission rate for HF was lower if ΔPC > median compared with ΔPC ≤ median for all parameters evaluated in both study groups with the most pronounced difference predicted by LI ( P < 0.01). Net reclassification improvement analysis showed that adding LI to the traditional clinical and laboratory parameters improved the predictive power significantly. Conclusions: The extent of ΔPC improvement, primarily the LI based, during HF‐hospitalization, and study group allocation strongly predicted readmission and event‐free survival time.